WEB-RESOURCES IN NUCLEAR SCIENCE AND TECHNOLOGY - B. S., Kademani; Kumar, Anil; Sagar, Anil; Surwase, Ganesh; Kumar, Vijai (Malaysian Journal of Library and Information Science, 2007)
This paper attempts to analyse the growth and development of web-resources in Nuclear Science and Technology as reflected in the International Nuclear Information System (INIS) (1996-2005) database. During 1996-2005, a total of 102,720 publications appeared in 1,526 web-resources contributed by the nuclear scientists in various areas of research namely, Physics (52,590), Other Aspects of Nuclear and Non Nuclear Energy (23,148), Life and Environmental Sciences (13,843), Engineering and Technology (10,380), and Chemistry, Materials and Earth Sciences (2,759). The publications in webresources have started appearing in the INIS database in 1996 with three publications. The highest number of publications in web-resources published were 25,813 in 2005. The average number of publications in web-resources published per year were 10,272. The top websites were http://www.iop.org with 30,711 publications, followed by https://www.osti.gov with 25,241 publications, and http://www.dx.doi.org with 8,569 publications. The websites with the domain name .org have published 51,602 followed by .gov with 26,613 publications and .jp with 6,565 publications. More than 91.8 percent of publications in web-resources were in English. More than 45 percent of the webresources were published in journals followed by reports (41.66%). The most preferred web-journals by the scientists were Journal of Physics-Condensed Matter with 6,677 publications, followed by Journal of Physics-A with 5,186 publications and Journal of High Energy Physics with 4,799 publications. Also analysed were the locations of webresources in various fields in a record in the database.